Investigation of invariant sets with random perturbations with the use of the Lyapunov function - Stanzhitskii, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider invariant sets of the form V(t, x) = 0, where V(t, x) is the Lyapunov function of the corresponding deterministic system.